Priming seeds for the future: Plant immune memory and application in crop protection - Yang, Zige; Zhi, Pengfei; Chang, Cheng (Frontiers in Plant Science, 2022)
Plants have evolved adaptive strategies to cope with pathogen infections that seriously threaten plant viability and crop productivity. Upon the perception of invading pathogens, the plant immune system is primed, establishing an immune memory that allows primed plants to respond more efficiently to the upcoming pathogen attacks. Physiological, transcriptional, metabolic and epigenetic changes are induced during defense priming, which is essential to the establishment and maintenance of plant immune memory. As an environmental-friendly technique in crop protection, seed priming could effectively induce plant immune memory. In this review, we highlighted the recent advances in the establishment and maintenance mechanisms of plant defense priming and the immune memory associated, and discussed strategies and challenges in exploiting seed priming on crops to enhance disease resistance.